Application of the TDR measuring technique for in-situ measurements using surface probes - Suchorab, Zbigniew; Pavlík , Zbyšek; Černý, Robert (Budownictwo i Architektura / Civil and Architectural Engineering, 2011)
The article presents the possibility of in-situ measurements of building barriers moisture using the TDR technique (Time Domain Reflectometry). To minimize the previous disadvantages of the described method – invasive character, several prototypes of the surface probes were manufactured. With such a sensor solution it was possible to conduct the non-invasive measurements using the full TDR method potential – quick measurements and no sensitivity of salinity influence. The measurements were conducted on the brickworks made of red ceramic brick at the old building located on 1st of May Street in Lublin.